2014
DOI: 10.1007/128_2013_497
|View full text |Cite
|
Sign up to set email alerts
|

General Computational Algorithms for Ab Initio Crystal Structure Prediction for Organic Molecules

Abstract: The prediction of the possible crystal structure(s) of organic molecules is an important activity for the pharmaceutical and agrochemical industries, among others, due to the prevalence of crystalline products. This chapter considers the general requirements that crystal structure prediction (CSP) methodologies need to fulfil in order to be able to achieve reliable predictions over a wide range of organic systems. It also reviews the current status of a multistage CSP methodology that has recently proved succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 81 publications
0
37
0
Order By: Relevance
“…1) and often arises from the presence of rotatable bonds (Cruz-Cabeza and Bernstein, 2014) with a deformation energy of the same order of magnitude as the energy change on packing (Kazantsev et al, 2011a). It is thus essential to account accurately for molecular flexibility during the course of energy minimization; a discussion of the pitfalls of neglecting or overly restricting flexibility can be found in Pantelides et al (2014). The need to explore conformational variation greatly increases the complexity of the optimization problem and has been a key driver for recent theoretical and algorithmic developments of our CSP framework.…”
Section: Overview Of the Csp Methodologymentioning
confidence: 98%
See 4 more Smart Citations
“…1) and often arises from the presence of rotatable bonds (Cruz-Cabeza and Bernstein, 2014) with a deformation energy of the same order of magnitude as the energy change on packing (Kazantsev et al, 2011a). It is thus essential to account accurately for molecular flexibility during the course of energy minimization; a discussion of the pitfalls of neglecting or overly restricting flexibility can be found in Pantelides et al (2014). The need to explore conformational variation greatly increases the complexity of the optimization problem and has been a key driver for recent theoretical and algorithmic developments of our CSP framework.…”
Section: Overview Of the Csp Methodologymentioning
confidence: 98%
“…In addition, it is necessary to be able to predict the crystal structures of salts, co-crystals and solvates as such systems are frequently used to enhance product effectiveness or to facilitate manufacturing. In a recent publication (Pantelides et al, 2014), we set out the design requirements that systematic CSP methodologies should meet in order to find wide applicability in practice, such as (i) a high degree of automation, with limited dependence on user insight; (ii) a consistent and general physical basis; (iii) a high degree of reliability; (iv) a high degree of accuracy, but with reasonable computational cost. This last requirement is particularly challenging: experience in crystal structure prediction has shown that it is essential to carry out an exhaustive search of the energy landscape covering millions of potential structures, and that the relative energies of computed crystal structures are highly dependent on the accuracy of the energy model, with electronic structure calculations providing the most reliable results (Bardwell et al, 2011).…”
Section: The Csp Problemmentioning
confidence: 99%
See 3 more Smart Citations